Rancang Bangun Aplikasi Game Petualangan Wisata Aceh pada Perangkat Mobile - Mursyidin, Mursyidin (PTE FTK UIN Ar-Raniry, 2017)
Aceh province has a myriad of beautiful locations or attractions but still a small part that is visited by tourists both local and foreign tourists. This is due to the lack of promotion of the beauty of tourist attractions in Aceh. Game is one of the media that can be used to promote the beauty and tourist location in Aceh. The use of games for adventure games such as adventure to find tourist attractions is a type of game that can be used as a media campaign. This game is expected to make it easier for the public to get to know aceh from the tourist objects and culture in it so that the curiosity of the people about Aceh province will increase.